Rater Competency and Compliance to Accuracy in Conducting Performance Appraisal in the Malaysian Public Sector - Hii, Linda (APTIBM, 2010)
This conceptual paper proposes that raters’ competency and compliance to accuracy are not just a function of raters’ personal factors but they are also influenced by a host of other contextual factors in conducting a good performance appraisal. Rater personal factors identified are appraisal-related experience, amount of appraisal-related training received and rater personality. The contextual influences on raters’ performance are: raters’ perception of their ability to appraise (PASE) and Perceived System Knowledge (PSK) and Performance Appraisal Discomfort (PAD). It is further argued that a competent rater is more compliant to achieve rating accuracy. The researcher aims to test this model in the Malaysian Public Sector.